S70 Clinical effectiveness results from the first interim analysis of the VOCAL study; an observational study of ivacaftor in patients with cystic fibrosis and selected non-G551D gating mutations. (December 2018) - Simmonds, NJ; Castellani, C; Colombo, C; van der Ent, K; Kaviya, A; Hassan, M; DeSouza, C; Kinnman, N
Abstract : Introduction and objectives: In a prior Phase 3 trial (KONNECTION), CF patients with a non- G551D gating mutation showed improvements in pulmonary and systemic outcomes with ivacaftor (IVA). VOCAL is an ongoing multinational (UK, IT, NL) observational study to assess real-world effectiveness of IVA in CF patients with a non- G551D gating mutation ( G178R, S549N, S549R, G551S, G1244E, S1251N, S1255P or G1349D ). Methods: VOCAL has 4 years planned prospective data collection from enrollment. In this interim analysis, outcomes included percent predicted (pp) FEV1, pulmonary exacerbations (PEx), BMI, mortality and organ transplantation, evaluated for 12 months both before and after IVA initiation. Baseline was IVA initiation date. A mixed model for repeated measures for continuous outcomes and a negative binomial model for PEx was used. Results: 71 of 73 enrolled patients completed 12 months treatment: 25 (34%) male, mean (SD) age 26.9 (13.5) years, 23 (32%)<18 years old, mean (SD) baseline ppFEV1 64.7% (24.5). There was significant improvement in absolute ppFEV1 at 6 months, sustained over 12 months (Least Squares [LS] Mean Change [MC] 10.6%; p<0.0001) with significant change (p<0.01) in absolute ppFEV1 annual rate of decline from –3.01%/year pre-IVA to –0.06%/year post-IVA (ppFEV1 measures in first 30 days of IVA related to initial ppFEV1 increase were excluded). Significant reduction in PEx event rate per patient year was observed: 0.81 pre-IVA to 0.24 post-IVA (rate ratio [RR] 0.29; 95% CI 0.15, 0.56). Improvement from baseline at 12 months in BMI (LS MC: 1.0 Kg/m 2 ) for patients aged ≥20 years and BMI- z score for patients<20 years (LS MC 0.6) was significant (p<0.0001). There was one death unrelated to IVA and no transplants. No new safety signals were identified. Conclusion: Consistent with KONNECTION, real-world use of IVA in CF patients with a non- G551D gating mutation demonstrated significant and sustained improvements in ppFEV1, PEx and BMI. Reduction in ppFEV1 rate of decline indicates IVA is a disease-modifying therapy for treating CF. This abstract was previously presented at the 2018 ECFS Congress in Belgrade and is available online in Journal of Cystic Fibrosis (Volume 17, Supplement 3, pp. S10, https://www.cysticfibrosisjournal.com/article/S1569-1993(18)30146-2/abstract) Sponsored by Vertex Pharmaceuticals Incorporated